Can cognitive behaviour therapy beneficially influence arousal mechanisms in psychosis?. (13th August 2015) - Howells, Fleur M.; Baldwin, David S.; Kingdon, David G.
Abstract : Cognitive behavioural therapy for psychosis (CBTp) is an approved adjunct therapy for patients with psychotic disorders; however, we do not fully understand the neurobiological effects that this therapy may exert. Arousal, as measured by electroencephalography (EEG), provides a useful electrophysiological marker for assessing psychotic disorders. EEG studies may therefore serve as a useful measure for assessing the underlying effects of CBTp in psychotic disorders. Copyright © 2015 John Wiley & Sons, Ltd.